1986
DOI: 10.1161/01.res.59.3.237
|View full text |Cite
|
Sign up to set email alerts
|

Renal and systemic hemodynamic effects of synthetic atrial natriuretic peptide in the anesthetized rat.

Abstract: To characterize the hemodynamic events responsible for alterations in renal function during administration of atrial natriuretic peptide, we studied the systemic, renal, and glomerular circulatory effects of intravenous rANP[126-149], administered as a 4 micrograms/kg prime and 0.5 microgram/kg per minute continuous infusion in anesthetized, euvolemic rats. With this protocol, a small decline in mean systemic arterial blood pressure occurred in the context of markedly enhanced urinary sodium excretion, hemocon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
3
1

Year Published

2000
2000
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(61 citation statements)
references
References 38 publications
1
56
3
1
Order By: Relevance
“…Using a similar experimental design, Eiskjaer et al (1996) and Janssen et al (1994) in adult humans, as well as Semmekrot et al (1990) in rabbits, observed these indices to decrease. On the other hand, no changes in renal blood (plasma) flow were found by Brown and Corr (1987) in humans, and by Dunn et al (1986) and Garcia-Estan and Roman (1990) in adult rats.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Using a similar experimental design, Eiskjaer et al (1996) and Janssen et al (1994) in adult humans, as well as Semmekrot et al (1990) in rabbits, observed these indices to decrease. On the other hand, no changes in renal blood (plasma) flow were found by Brown and Corr (1987) in humans, and by Dunn et al (1986) and Garcia-Estan and Roman (1990) in adult rats.…”
Section: Discussionmentioning
confidence: 89%
“…Conversely, Janssen et al (1994) in adult humans, Robillard et al (1988) in adult sheep, Seino et al (1988) in adult rabbits, andChevalier et al (1988) in adult rats, observed an increased glomerular filtration rate after administration of exogenous ANP. According to Dunn et al (1986) and Marin-Grez et al (1986), enhanced GFR may be a result of haemodynamics changes in the blood vessels of the glomeruli which lead to elevated glomerular filtration pressure. Conversely, Semmekrot et al (1990) observed decreasing GFR in young (4 -11 days old) and adult rabbits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,35 ANP increases efferent glomerular arteriolar tone, one mechanism by which GFR may be maintained in the current setting. 36,37 Our study did not allow direct comparison of omapatrilat with pure ACE inhibition. Nevertheless, there is clear evidence of dual neutral endopeptidase and ACE inhibition.…”
Section: Troughton Et Al Omapatrilat In Mild and Severe Heart Failurementioning
confidence: 98%
“…34,35 Both ANP and BNP also improve renal blood flow via afferent arteriolar vasodilation and efferent arteriolar vasoconstriction. 36,37 There is also a direct effect on the collecting duct, leading to increased sodium excretion. 38 C-type natriuretic peptide acts primarily through a different receptor and plays a little known role in CHF.…”
Section: Physiology Of B-type Natriuretic Peptidementioning
confidence: 99%